Phyllocnistis podocarpa sp. nov. (Lepidoptera, Gracillariidae), a buddhist pine leaf-miner from Japan: taxonomy, DNA barcodes, damage and parasitoids - Liu, Tengteng; Sun, Jie; Cai, Bo; Wu, Ying (Zootaxa, 2018)
Phyllocnistis podocarpa sp. nov., is described from mines in Podocarpus macrophyllus (Family Podocarpaceae). The host plant P. macrophyllus, also known as buddhist pine on the IUCN Red List, is a noticeable garden plant and thus of high economic value. Buddhist pine has been introduced to many other countries from its native habitat in southern Japan. Special attention has been paid for it during the overseas import in China. The morphology of the pupae of P. podocarpa, particularly the frontal process of the head and the spine clusters on terga, ones of the most useful diagnostic characters for species identification of Phyllocnistis on morphology, is demonstrated using SEM. Two parasitoid species of Eulophidae (Hymenoptera) are identified and illustrated. COI barcode sequences are provided along with a Neighbor Joining Tree covering related species for aiding identification.